Nursing Care for CKD On HD Patients at the Inpatient Facility of Royal Prima Hospital Medan in 2026 - Frisandia Gulo; Widya Santi Manggalika; S. Cristin Tambunan; Agnes Yolanda S; Cheriza Addara; Robin Ferdiansyah Sitopu (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Chronic Kidney Disease (CKD) is a progressive kidney function disorder that causes the kidneys to be unable to maintain the balance of fluids, electrolytes, and remove the body's metabolic waste optimally. Patients with end-stage CKD generally require lifelong hemodialysis (HD) therapy to maintain quality of life. This study aims to describe nursing care for CKD on HD patients at the Inpatient Installation of Royal Prima Hospital Medan in 2026. The method used is a case study with a nursing process approach including nursing assessment, diagnosis, intervention, implementation, and evaluation. The subject of the study was Mr. N aged 84 years with a medical diagnosis of regular CKD on HD accompanied by anemia. Data were obtained through interviews, observations, physical examinations, and documentation studies. The results of the study showed that the patient experienced shortness of breath, edema in both legs, nausea and vomiting, decreased appetite, weakness, and decreased urine output. Laboratory tests showed Hb 7.0 g/dL, urea 187 mg/dL, and creatinine 10.79 mg/dL. Established nursing diagnoses are that hypervolemia is associated with excess fluid intake, ineffective breathing patterns are associated with obstruction of breathing efforts, and nausea is associated with biochemical disorders due to increased urea. The nursing interventions provided include hypervolemia management, respiration monitoring, and vomiting management according to SDKI, SLKI, and SIKI for 3×24 hours. Evaluation showed that the problem of ineffective breathing pattern and nausea was resolved, while partially resolved hypervolemia was characterized by a decrease in edema to degree I and continued with a regular HD program. Comprehensive and continuous nursing care is indispensable to improve the clinical conditions and quality of life of CKD on HD patients.